Somatic Embryogenesis and Plant Regeneration from the Apical Meristem of Wrukwona Napiergrass (Pennisetum purpureum) Treated with Thidiozuron and Cupric Sulfate - N. Umami; A. N. Respati; M. M. Rahman; K. Umpuch; T. Gondo (Faculty of Animal Science, Bogor Agricultural University, 2022)
This study focused on the effectiveness of somatic embryogenesis and regenerated plant in Wrukwona napiergrass. Previously, we studied in vitro propagation of 4 cultivars of napiergrass (Pennisetum purpureum) and showed that only 3.3% of Wrukwona cultivar formed embryogenic callus on day 30 and 21.7% on day 60 of incubation. To improve callus formation performance, it is necessary to develop a special propagation method for Wrukwona cultivar in terms of various growth regulators and additional compounds. This study used several rates of 2.4-dichlorophenoxyacetic acid (2.4-D), benzyl amino purine (BAP), and thidiozuron (TDZ). The result showed that the use of medium Murashige & Skoog (MS) with 2.4-D and BAP at a high ratio of 2.4-D, and TDZ 2 µM formed 78.6% embryogenic callus on day 60th and no albino was found in the regenerated plant. The best combination of growth promotor for embryogenic callus formation was 3 mg L-1 2.4-D, 0.5 mg L-1 BAP, and 2 µM TDZ. Callus proliferation with MS media added with 3 mg L-1 2.4-D, 0.5 mg L-1 BAP, 2 µM TDZ, and 5 µM CuSO4 gave the best proliferation results, with regeneration reaching 65%. All regenerants successfully grew in soil. It can be concluded that somatic embryogenesis of P. purpureum cv. Wrukwona can be produced from MS culture medium using 2 mg L-1 2.4-D, 0.5 mg L-1 BAP, and 2 µM TDZ. Effective multiplication was carried out by adding 5 µM CuSO4 to the same medium as the embryogenic callus formation, and effective regeneration was carried out with MS media containing 2 mg L-1 BAP.